Comparative study on weathering durability property of phenol formaldehyde resin modified sweetgum and southern pine specimens - Hu, Wengang; Wan, Hui (Maderas. Ciencia y Tecnología, 2021)
The effects of low molecular weight phenol formaldehyde resin on weathering durability property of sweetgum (Liquidambar styraciflua) and southern pine (Pinus taeda) specimens were studied using six wet-dry cycles with ultraviolet light accelerated weathering test following ASTM D2898-10 via evaluating the water repellent efficiency, dimensional stability, and crack formation of wood. The results showed that 1) the water repellent efficiency of treated quarter-sawn sweetgum specimens was higher than those of treated quarter-sawn and flat-sawn southern pine specimens; 2) the dimensional stabilities of sweetgum and southern pine specimens were all improved by impregnating low molecular weight phenol formaldehyde resin, especially for sweetgum; 3) there were clearly more cracks on exposed ends and surfaces of all treated sweetgum and southern pine specimens than those on control ones, indicating that the low molecular weight phenol formaldehyde resin modification used in this study were not able to improve the anti-cracking properties of sweetgum and southern pine specimens. Generally, the sweetgum was more suitable to be impregnated with low molecular weight phenol formaldehyde resin than southern pine with the procedure described according to dimensional stability and water repellent efficiency, in order to improve the weathering durability.